AN EXISTENCE RESULT FOR AN ELLIPTIC PROBLEM INVOLVING A FOURTH ORDER OPERATOR - Ourraoui, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper, we prove the existence of solutions for a $p$-Biharmonic in bounded domain, by applying the Bohnenblust-Karlin fixed point theorem. The regularity of a such solution is also established.